GENETIC VARIABILITY AND POPULATION STRUCTURE OF GROUPER (Epinephelus suillus) FROM MAKASSAR STRAIT AND BONE BAY, SOUTH SULAWESI, INDONESIA - Andi Parenrengi; Andi Tenriulo (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2008)
Random Amplified Polymorphic DNA (RAPD) was employed to determine the genetic variability and population structure of grouper (Epinephelus suillus) from Makassar Strait and Bone Bay, South Sulawesi, Indonesia. Genomic DNA was isolated from preserved muscle tissue using Phenol-Chloroform technique. Among 24-screened arbitrary primers, ten primers (OPA-02, OPA-06, OPA-08, OPA-10, OPA-15, OPA-16, OPA-17, OPA-18, OPA-19 and CA-05) were selected to generate RAPD fingerprinting of grouper populations. The ten primers generated a total of 212 fragments (loci) and 120 polymorphic fragments in their size ranging from 250 to 2,500bp. The high polymorphism (60%) was obtained from Makassar population followed by Bone (59%) and Pare-Pare populations (50%). Similarity index of individuals was 0.86±0.07 for Pare-Pare, 0.80±0.11 for Makassar and 0.82±0.07 for Bone population. Fifteen fragments from ten primes were identified as species-specific markers of E. suillus. The UPGMA cluster analysis showed that the dendrogram seemed to be clustered according to their geographical location, where Pare-Pare population was genetically closer to Makassar population (D=0.20) than to Bone population (D=0.24).